1998
DOI: 10.1093/jpepsy/23.4.239
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mothers' Sense of Empowerment oh the Metabolic Control of Their Children With Juvenile Diabetes

Abstract: The findings support the importance of developing and enhancing the parents' sense of empowerment toward better adherence and metabolic control of their children's IDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…This concern could be particularly salient given that most fatal reactions occur outside the home. 4,21 Given the extant literature in other pediatric populations identifying associations between parent-perceived competence or self-efficacy and decreased parental distress, 16,22 the present empowerment and QOL findings combine to underline a fundamental difference between the nature of food allergy and other chronic conditionsdthe constant risk, real or perceived, of potentially fatal anaphylaxis occurring outside the sphere of parental influence.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This concern could be particularly salient given that most fatal reactions occur outside the home. 4,21 Given the extant literature in other pediatric populations identifying associations between parent-perceived competence or self-efficacy and decreased parental distress, 16,22 the present empowerment and QOL findings combine to underline a fundamental difference between the nature of food allergy and other chronic conditionsdthe constant risk, real or perceived, of potentially fatal anaphylaxis occurring outside the sphere of parental influence.…”
Section: Discussionmentioning
confidence: 78%
“…Previous work has found that parents' perceived competence with regard to their ability to manage their child's chronic condition promotes adaptive family functioning, increases medication adherence, and decreases parental distress. 6,16,40 The present sample, with a large number of married couples, which presumably would allow for greater cohesion for the couple in caring for the child, could represent a best-case scenario in which mothers and fathers could ideally know the risks and responsibilities of allergy reactions in their offspring, thereby shouldering the burden equally between them. Nevertheless, significant differences were found between maternal and paternal self-reported empowerment and confidence in their ability to implement that knowledge in the effective management of their child's food allergy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FES has been adapted and used in several studies (Florian & Elad, 1998;Walsh & Lord, 2004), including research with women who were battered (Itzhaky & Porat, 2005). The original scale has demonstrated reliability and validity with a kappa coefficient of .77 and alpha coefficients ranging from .87 to .88 for each of the subscales (Koren et al, 1992).…”
Section: Dependent Variable: Economic Empowermentmentioning
confidence: 99%
“…10 Appropriate use of EpiPen constitutes proper treatment of food-induced anaphylaxis, although the outcome is more difficult to measure than glycosylated hemoglobin for patients with IDDM. The referenced Israeli study 10 used, among other validated questionnaires, the Family Empowerment Scale (FES), 11 an instrument originally designed for families of children with emotional disabilities.…”
Section: Explored Parentalmentioning
confidence: 99%